ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS NASABAH DITINJAU DARI DIMENSI RELATIONSHIP MARKETING, KUALITAS LAYANAN DAN PERSONAL SELLING (STUDI DI BANK BRI CABANG TULUNGAGUNG) - Bayu Dwihandrianto (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The formation of customer loyalty can be implemented through a focus on delivering value and increasing customer loyalty. Loyalty means returning and returning customers to conduct business transactions (purchases), although it may be that the company's product is not the best product in the market or has the lowest price. This "irrational" customer behavior can be explained by a view that a "good relationship" with the customer is the key to a company's success in retaining customers.This research is a correlational quantitative research. The population of this research is bank customer of BRI branch of tulungagung by taking sample as many as 48 respondents. The sampling technique was performed by random sampling technique. Methods of data collection using a questionnaire. Result of data analysis in this research show: There is influence from relationship marketing to customer loyalty at bank BRI Tulungagung branch. There is influence of service quality on customer loyalty at BRI bank of Tulungagung branch. There is influence from persona selling to customer loyalty at bank of branch of tulungagung. There is influence of relationship relationship marketing , quality of service and personal selling to customer loyalty at bank BRI branch of tulungagung.The results of this study can be used as reference materials in the effort to develop various policies and plans to improve customer loyalty, and improve relationship (relationship), service quality and personal selling to customers of BRI bank branch of tulungagung..